A rare case of pseudoaneurysmal hemorrhage, necrotizing fasciitis, and costochondritis after pancreaticoduodenectomy - Lulu Li; Kyohei Abe; Tomoyoshi Okamoto; Michinori Matsumoto; Yasuro Futagawa; Masaru Kanehira; Toru Ikegami (Surgical Case Reports, 2022)
Abstract Background Necrotizing fasciitis after pancreaticoduodenectomy (PD) has never been reported. We experienced a case of necrotizing fasciitis caused by pseudoaneurysmal hemorrhage after PD. Case presentation A 72-year-old male was diagnosed with cholangiocarcinoma and underwent PD. Bile leakage was detected postoperatively, conservatively resolved, and the patient was discharged on the 36th day after surgery. On the 42nd day after surgery, a pseudoaneurysm of the gastroduodenal artery ruptured. Transcatheter arterial embolization was performed for hemostasis: however, a large intra-abdominal abscess caused by an infected hematoma was recognized. On the 57th day after surgery, the patient developed necrotizing fasciitis. He underwent debridement with skin reconstruction using a latissimus dorsi flap and skin transplantation. Costochondritis and liver metastasis were detected on the 267th day after surgery. Infection was controlled by rib cartilage resection, debridement, and negative pressure wound therapy. Chemotherapy involving gemcitabine and cisplatin was initiated on the 460th day after the initial surgery with a partial response (PR) and was continued for more than one year. Conclusions We herein reported a rare case of necrotizing fasciitis following hematoma infection after PD that was treated using multidisciplinary therapy with PR following chemotherapy.